El oscuro invierno : primer caso del sargento McAvoy - Mark, David John, 1977- (Nuevos tiempos (Madrid, Spain), 2013)
Investigating a series of suspicious deaths and discovering that each victim was the sole survivor of a tragedy, Detective Sergeant Aector McAvoy of the northern England port of Hull struggles to balance the demands of the case with the needs of his beloved family.